THE USE OF DIGITAL OUTCROP MODEL (DOM) FOR FASIES HETEROGENITY ANALYSIS IN MAHAKAM DELTA AREA, KUTEI BASIN, EAST KALIMANTAN - MADE SUDIANA PUTRA (NIM. 22015303), I
The use of digital photography in the outcrop study proved to be very useful in capturing sedimentological characteristics in high details and accuracy, improving our capabilities in understanding the heterogeneities of the reservoir rocks formation. The utilization of digital camera equipped with Global Positioning Satellites (GPS) and Global Navigation Satellite System (GLONASS) receiver, make it possible to determine the position and geometry of the outcrops during field works. The outcrops often found on the location that is difficult to reach, such as on top of the hill, on the cliff or in hazardous locations that make it difficult to visit or to take sample for further examination. Therefore the use of unmanned aerial vehicle (drone) is very useful to study these outcrops and to recognize their distribution in the field. Every type of rock has its specific color characteristics based on its composition, mineral contents, and the mechanical/chemical processes in which the rocks are formed, and also affected by weathering process as soon as the rocks exposed to the surface. This color characteristics can be represented by using histogram of its primary color, i.e. red, green and blue (RGB). Digital photo of the outcrops can be processed to construct a digital outcrop model in 2D or 3D that accurately represent the color, characteristics and geometry of the outcrops. Digital photo analysis based on RGB color distribution of these outcrops can be used to find out the similarities of their lithofacies. RGB histogram generated from digital photos of the outcrops can be compared using various histogram comparison methods, to discover their similarities and to predict their lithofacies and their distribution in the field.